Polymeric foams. - Gupta, Ram K. (ACS symposium series, 2023)
"Polymeric foams are an important industrial product category with wide applications across many market sectors including automotive, thermal insulation, sound insulation, biomedical, energy, and sensors, to name a few. This book will cover the materials, chemistry, technology, and applications of various types of polymeric foams, including an overview of the foaming mechanism, technologies, applications, and current challenges. Volume 1 focuses on the fundamentals and types of foams, while volume 2 addresses applications. Currently, no book covers all aspects of polymeric foams; this material fills a void on this timely topic and will be a valuable resource for polymer and materials scientists and chemists working in these areas."--